Clinical manifestations of gastrointestinal form of food allergy in children and approaches to its diagnosis - Yu.R. Chernysh; O.M. Okhotnikova (Zaslavsky O.Yu., 2017)
Gastrointestinal food allergy is caused by the development of allergic inflammation in the mucosa of the gastrointestinal tract. The mechanisms of this inflammation are immunogflobulin E (IgE)-mediated (oral allergic syndrome, immediate gastrointestinal hypersensitivity), non-IgE-mediated (protein-induced enterocolitis syndrome, protein-induced enteropathy, protein-induced allergic proctocolitis) and mixed IgE- and non-IgE-mediated reactions (eosinophilic esophagitis, eosinophilic gastritis and eosinophilic gastroenteritis). Gastrointestinal manifestations of food allergy are also combined with symptoms of atopic diseases, more often with atopic dermatitis, urticaria and angioedema. Clinical manifestations of allergic lesions of the gastrointestinal tract are different and non-specific. Common signs of gastrointestinal allergy include: vomiting (occurs from a few minutes to 4-6 hours after eating); сolic (immediately or several hours after eating); constipation; diarrhea; refusal of food (from a specific product or complete refusal to eat); abdominal pain; flatulence, the presence of mucus and eosinophils in the stool; poor appetite; headache. Differential diagnosis of gastrointestinal food allergy should be carried out with diseases such as disease and abnormalities in the development of the digestive system, mental and metabolic disorders, intoxications, infectious diseases, pancreatic endocrine gland failure, celiac disease, cystic fibrosis, immunodeficiencies, disaccharidic insufficiency, side effects of medications, endocrine pathology, irritable bowel syndrome. Methods for diagnosing gastrointestinal allergy, which currently exist, are limited and imperfect. This requires further scientific researches aimed at timely detection of this pathology, prevention in genetically predisposed children, development of optimal diagnostic algorithms, prevention of the progression of clinical manifestations, the choice of individual diet therapy and adequate medication. The literature review presents modern views on the diagnosis of gastrointestinal food allergy in children. The article details clinical manifestations and diagnostic approaches to certain types of gastrointestinal allergy depending on the mechanism of their occurrence.